The Analysis Study of Impact of Maternal Age towards Stunting in Children: A Systematic Review and Metaanalysis Studies - Hidayat, Nafian; Armeilia, Rilie; Imami, Khairul; Saputra, Andri; Rosa, Elvina (International Medical Journal Corp. Ltd, 2024)
Background : Stunting has been a chronic worldwide problem which affects children growth and development, finally their productivity and future. Maternal age was one of determining factors, yet still uncertain and somewhat neglected. Method : Systematic review based on PRISMA statement was conducted. Critical appraisal was done with The Joanna-Briggs Institute critical appraisal tools. Studies’ characteristics and results were extracted for qualitative and quantitative analysis. Quantitative analysis was done with random- of fixed-effect model based on heterogeneity. Results: A total of 18 good quality studies involving 422,750 mothers and their respective children were included. Qualitative analysis showed that younger and older maternal age were linked with stunting risk increment. However, quantitative analysis found that only younger age (< 20 years old) was related to increase of stunting risk (OR = 1.31; 95% CI = 1.05 – 1.63). Conclusion: Younger maternal age (< 20 years old) was related to development of stunting in children. More studies should be conducted to provide more evidence in other age groups.